2019
DOI: 10.26434/chemrxiv.6353402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Architectured helically coiled scaffolds from elastomeric poly(butylene succinate) (PBS) copolyester via wet electrospinning

Abstract: <div><div><div><p>Electrospinning is one of the most investigated methods used to produce polymeric fiber structures that mimic the morphology of native extracellular matrix. These structures have been extensively studied in the context of scaffolds for tissue regeneration. However, the compactness of materials obtained by traditional electrospinning, collected as two-dimensional non-woven scaffolds, can limit cell infiltration and tissue ingrowth. In addition, for applications … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…In this range, adhesion complexes are dynamic and experiments with polyacrylamide gels of various stiffness have also indicated that modulus values <20 kPa favor cell motility (Pelham and Wang, 1997). Thus, our results here help explain our prior findings of robust fibroblast infiltration and proliferation within electrospun 3D scaffolds of PBS-DLS 7030 copolymer (Sonseca et al, 2018), despite the lack of biofunctionality of the polymer itself: the adsorption of provisional matrix proteins such as Fg and Fn from the serum-containing cell culture media likely facilitated the favorable cell-scaffold interactions.…”
Section: Implications and Limitationssupporting
confidence: 79%
See 1 more Smart Citation
“…In this range, adhesion complexes are dynamic and experiments with polyacrylamide gels of various stiffness have also indicated that modulus values <20 kPa favor cell motility (Pelham and Wang, 1997). Thus, our results here help explain our prior findings of robust fibroblast infiltration and proliferation within electrospun 3D scaffolds of PBS-DLS 7030 copolymer (Sonseca et al, 2018), despite the lack of biofunctionality of the polymer itself: the adsorption of provisional matrix proteins such as Fg and Fn from the serum-containing cell culture media likely facilitated the favorable cell-scaffold interactions.…”
Section: Implications and Limitationssupporting
confidence: 79%
“…This family of copolymers, with varying hard to soft segment ratios, offers tunable mechanical properties typical of thermoplastic elastomers. More recently, our work with closely related PBS copolymers with DLS soft segments synthesized with enzymatic catalyst, has demonstrated the potential of these copolyesters for soft tissue engineering, as they are readily electrospinnable into 2D and 3D scaffolds and possess attractive mechanical and degradation properties (Sonseca and El Fray, 2017;Sonseca et al, 2018;Wcisłek et al, 2018). It is with these applications in mind, that we set out to study the adsorption of fibrinogen and fibronectin on PBS homopolymer and PBS-DLS copolymers with varying weight ratios (100:0, 70:30, 60:40, 50:50) of hard to soft segments.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, biopolymers have a great potential in biomedical and packaging applications [ 4 ]. A variety of biodegradable polymers have been tested, such as poly(lactic acid), polyhydroxyalkanoates, poly(ε-caprolactone), poly(butylene adipate-co-butylene terephthalate), and poly(butylene succinate) [ 3 , 4 , 6 , 8 , 12 , 13 , 14 ]. An interest in the mentioned polymers for food packaging applications has increased in the last two decades, posing one of the types of sustainable packaging materials.…”
Section: Introductionmentioning
confidence: 99%
“…Among the biodegradable aliphatic polyesters, poly(butylene succinate) (PBS) has great potential for commercial applications due to its biodegradability, thermal stability, low melting point, relatively easy processibility in the industrial-scale manufacturing, and chemical resistance [ 3 , 4 , 6 , 8 , 10 , 13 , 14 ]. PBS is synthesized via a polycondensation process from succinic acid and 1,4-butanediol and consists of polymerized units of butylene succinate with repeating C 8 H 12 O 4 units [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation